Application of Progressive Materials for Rapid Prototyping Technology - Novakova-Marcincinova, Ludmila; Janak, Miroslav (Manufacturing Technology Journal, 2012)
In paper are presented basic information about common and progressive materials used for realization of products by Rapid Prototyping technology application. The initial state of material can come in either solid, liquid or powder state. In solid state it can come in various forms such as pellets, wire or laminates. The current range materials include paper, nylon, wax, resins, metals and ceramics. Last mentioned materials are used manly in application of Rapid Prototyping technology for rapid manufacturing of products or rapid production of tools - Rapid Tooling.
Keywords: Rapid Prototyping; rapid prototyping materials; rapid manufacturing